Peningkatan Sikap Rasa Ingin Tahu dan Prestasi Belajar Matematika Melalui Model Pembelajaran Matematika Realistik (PMR) di SD - Sri Muryaningsih (Universitas Muhammadiyah Bangka Belitung, 2020)
This study aims to improve the attitude of curiosity and learning achievement of students in mathematics through realistic mathematics learning models. This type of research is Classroom Action Research (CAR) which consists of two cycles, one cycle consisting of two meetings. The subjects of the study were students of grade V SD UMP. The stages of activities in each cycle consist of planning, action, observation, and reflection. Curiosity data collection using the student's curiosity observation sheet while collecting students' learning achievement data using an evaluation sheet given at the end of each meeting. Based on the results of the study show a realistic mathematical learning model (PMR) can increase the attitude of curiosity and student achievement on the material around and flat area in grade IV SD UMP.